IMPLIKASI FIQH SOSIAL KYAI SAHAL MAHFUDH TERHADAP PEMBAHARUAN FIQH PESANTREN DI KAJEN PATI - Jamal Ma'mur (Program Studi Hukum Keluarga Islam, 2014)
H. MA. Sahal Mahfudh is social fiqh figure born and grown in pesantren. Social fiqh is the manifestation of his anxiety viewing stagnancy of fiqh pesantren discourse. Therefore, Kyai Sahal tries to stimulate pesantren’s fiqh discourse to be able to respond to the actual problems that occurred in the society. Kajen is pesantren’s village inhabited by many pesantrens. Kyai Sahal started social fiqh discourse in Kajen boldly despites the risks. In this village, ulama’s point of view is usually textual, absolute, and final in understanding texts in “kitab kuning”. Kyai Sahal tries to reform discourse of fiqh gradually. He develops fiqh discourse by proposing an effective solution of the problems of poverty and underdevelopment around Kajen. Kyai Sahal introduces social fiqh discourse in Kajen after proven its effectiveness in economic empowerment of pesantren. The younger ulama are the proponents of the development of fiqh discourse by Kyai Sahal. Kyai Sahal’s strategy has inspired society of Kajen to develop for the sake of development. Young cadres again become the main followers of Kyai Sahal’s brilliant idea. They study social fiqh of Kyai Sahal and establish research institutions to intensify this discourse. There are FK2P (Peantren’s Book Review Forum), ISFI (Progressive Fiqh Studies Institute), bulletin Reesala, and Social Fiqh Institute of STAI Mathali’ul Falah Kajen. These institutions examine seriously the development of fiqh discourse introduced by Kyai Sahal. This young generations are active to develop the idea if social Fiqh. Hopefully fiqh of pesantren is not obsolete and able to answer the challenges of the future. Kyai Sahal is perceived not only as an expert of ‘kitab kuning’, but also an expert of social modernity. He eventually becomes the idol of young generations as a locomotive of progressive changes in Kajen.Keywords: Kyai Sahal, Kajen, social fiqh